1997
DOI: 10.1007/s004390050500
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for gene conversion in the generation of extensive polymorphism in the promoter of the growth hormone gene

Abstract: The human growth hormone gene (GH-N) is located in a cluster of five highly homologous genes that are coordinately expressed in pituitary (GH-N) and in placental tissues (the chorionic-somatomammotropin-like gene, the GH-variant gene and the two chorionic somatomammotropin genes). Sequence analysis from position -162 to position +100 of the GH-N gene has revealed eight nucleotide polymorphisms with no significant difference in frequency between patients affected by isolated growth hormone deficiency and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 28 publications
7
56
0
5
Order By: Relevance
“…Moreover, in studying the relationships of members of a gene family, gene conversion is one commonly invoked explanation when orthologous genes do not form a monophylogeny. Previous studies have identified several gene conversion events in the evolution of the GH gene family (Hirt et al 1987, Chen et al 1989, Giordano et al 1997, Krawczak et al 1999, Horan et al 2003, Mendoza et al 2004, Ye et al 2005. In the present study, we also detected some cases of gene conversion events in NWM by a statistical method.…”
Section: Test Of Variable Among Lineages and Sites By The Maximum-liksupporting
confidence: 74%
“…Moreover, in studying the relationships of members of a gene family, gene conversion is one commonly invoked explanation when orthologous genes do not form a monophylogeny. Previous studies have identified several gene conversion events in the evolution of the GH gene family (Hirt et al 1987, Chen et al 1989, Giordano et al 1997, Krawczak et al 1999, Horan et al 2003, Mendoza et al 2004, Ye et al 2005. In the present study, we also detected some cases of gene conversion events in NWM by a statistical method.…”
Section: Test Of Variable Among Lineages and Sites By The Maximum-liksupporting
confidence: 74%
“…We identified a novel polymorphism, a transition from adenine to guanine at nt 69 (A69G), which has been reported as a mutation in patients who are short in stature. 18 Of the other nine SNPs reported in previous studies performed in this region, 13,14 three were common in the current population (Table 1). These 3 SNPs, along with the SNP at nt ϩ69 and the SNP in intron 4, were genotyped using the TaqMan assay (Applied Biosystems) for all participants.…”
Section: Laboratory Protocolsmentioning
confidence: 71%
“…12 The promoter and the proximal region are highly polymorphic, with 9 single-nucleotide polymorphisms (SNPs) reported within a 310 -base pair (bp) stretch. 13,14 It has been reported recently that these polymorphisms (in haplotypes) affect GH1 expression significantly. 13 In addition, an SNP located at bp 1169 (intron 4 [P-1]) of the GH1 gene has been linked to GH1 secretion in a trial involving prepubertal short children.…”
mentioning
confidence: 99%
“…In addition, it is possible that, owing to the low number of compared BAC clones, many SNPs may not have been discovered, particularly low-frequency SNPs. The increased polymorphism in segmental duplications can be explained either by gene conversion with other LCRs found in the genome (Giordano et al 1997;Hurles 2002;Hurles et al 2004) or by selective pressure on sequence diversification and suppression of deleterious recombination between LCR22-2 and LCR22-4.…”
Section: Genome Research 1491mentioning
confidence: 99%